Collaboration chercheur didacticien/enseignant et choix de l’enseignant en situation scolaire : une étude de cas en sciences de la Terre - Denise Orange Ravachol (Recherches en Éducation)
While managing students in the classroom, teachers usually do not make the choices they had previously planned, even when these choices originate from collaborations with science education researchers. Therefore, we are compelled to conduct a more in-depth study of the logic of the organization of the teaching practice. This was done through two geology teachers working with their 17-18 year-old students on the problem of the running of a subduction zone (convergent boundary where two tectonic plates collide). In order to understand the scientific knowledge building, we favour the theoretical framework of problematization, shared by the team including these teachers and two science education researchers. We do show that the collaborations lead the teachers have their students problematize, but it must be said that this problematization remains superficial, sporadic and is rapidly discarded for a logic of selection of the right answer. The constraints of school standards and the prevailing epistemology of the teaching staff seem to be decisive in these changing ways of teaching.